The Influence of Learning Methods and Learning Motivation on the Learning Outcomes of Basketball - Prasetya, Agung; Wardiah, Dessy; Junaidi, Ilham Arvan (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
The aim of this study was to investigate the impact of learning methods and motivation on basketball performance outcomes among eighth-grade students at SMP Negeri 07 Mukomuko. The research employed a quasi-experimental design to evaluate student motivation using descriptive and qualitative analysis, while basketball performance was assessed through quantitative analysis. The study population included 109 students enrolled in basketball classes at SMP Negeri 07 Mukomuko. The sample was 43 students. Data on learning motivation were gathered through questionnaires, and skill tests were used to evaluate learning outcomes. Data analysis was conducted using two-way analysis of variance (ANOVA) and the Tukey test. Prior to performing variance analysis, prerequisite tests were conducted to check for normality using the Lilliefors test and variance homogeneity using the Bartlett test, with a significance level set at α = 0.05. The results state that the inquiry teaching learning method is more effective in improving basketball playing skills than the peer teaching learning method. The group with a high level of motivation had better basketball playing skills compared to the group with a low level of motivation. There is an interaction between learning methods and learning motivation on improving basketball playing skills.